OPTIMIZATION OF TELECOMMUNICATION TRANSACTION DATABASE WITH NOSQL MEMCACHED - Riki Ramdani Saputra (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
Nowadays, more people depend on telecommunication access; therefore, providers are required to be able to provide convenience in providing services. Those including transaction services that can be carried out from various telecommunication facilities. These issues causing the transaction table to have a very-heavy workload because it is accessed from various applications, both web-based applications and smartphone applications. With the large number of transactions through web-based applications, it is required for the efficiency of the web transaction method in accessing the database. With the presence of the noSql method, the results of data calls (query) from the client can be stored on the server memory as temporary storage (cache). The goal is to make the transaction website remains responsive, even though it is accessed a lot and having repeated data calls (queries). By using the memcached method, transaction database performance can be suppressed by up to 5%.